2006
DOI: 10.1007/s11119-006-9021-x
|View full text |Cite
|
Sign up to set email alerts
|

Soil electrical conductivity as a function of soil water content and implications for soil mapping

Abstract: Apparent soil electrical conductivity (EC a ) has shown promise as a soil survey tool in the Midwestern United States, with a share of this interest coming from the precision agriculture community. To fully utilize the potential of EC a to map soils, a better understanding of temporal changes in EC a is needed. Therefore, this study was undertaken to compare temporal changes in soil EC a between different soils, to investigate the influence of changes in soil water content on soil EC a , and to explore the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
4
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(139 citation statements)
references
References 16 publications
4
126
4
5
Order By: Relevance
“…In a no-till corn/soybean fields low ECa values were observed at higher elevation compared to high ECa values at low elevation [49]. Brevik et al [7] concluded that ECa may increase with an increase in volumetric water content due to strong relation (R 2 = 0.70) between them. They also observed that higher elevation soil sampling locations had lower ECa values compared to lower elevations due to higher volumetric water content at lower elevation positions.…”
Section: Influence Of Topographic Position On Ecamentioning
confidence: 98%
See 2 more Smart Citations
“…In a no-till corn/soybean fields low ECa values were observed at higher elevation compared to high ECa values at low elevation [49]. Brevik et al [7] concluded that ECa may increase with an increase in volumetric water content due to strong relation (R 2 = 0.70) between them. They also observed that higher elevation soil sampling locations had lower ECa values compared to lower elevations due to higher volumetric water content at lower elevation positions.…”
Section: Influence Of Topographic Position On Ecamentioning
confidence: 98%
“…The EMI technique can measure apparent soil electrical conductivity (ECa) by inducing an electrical current in the soil [7]. This method provides a relatively accurate, non-invasive, fast and inexpensive measurement of ECa [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ability to quantify the soil environment, including parameters like pH, organic matter, and moisture content, at high spatial resolution remains challenging given the heterogeneity of soils. Grid soil sampling and electromagnetic soil mapping, which measure soil conductivity to estimate properties like salinity, water content, and organic matter, have proven useful in characterizing spatial soil variability (Mallarino and Wittry, 2004;Brevik et al, 2006;Sun et al, 2013;Guo et al, 2015b). These methods are not without their limitations though; both grid soil sampling and electromagnetic mapping are typically performed once per season, making it impossible to capture the dynamic nature of the soil-water profile.…”
Section: Envirotypingmentioning
confidence: 99%
“…However, such a relationship was not observed in the present study. Nonetheless, this behavior can be explained by the fact that ECa values are influenced by a combination of soil salts, mineralogy of the clay, and temperature of the soil (Brevik et al, 2006). Fig.…”
Section: Correlation Of Eca With Soil Attributesmentioning
confidence: 99%